The influence of college students’ career exploration on career maturity in Guangdong province, China: The moderating effect of future time perspective and mediated by professional commitment - Wu, Lingna; Chang, Yuan-Cheng (Edelweiss Applied Science and Technology, 2025)
Based on Social Cognitive Career Theory (SCCT), this study empirically explores how career exploration influences career maturity among college students in Guangdong Province, China, with a focus on the mediating role of professional commitment and the moderating role of future time perspective. Using convenience sampling, 588 valid questionnaires were collected from 16 universities across major cities in Guangdong. The moderated mediation model was tested using the SPSS PROCESS macro (Model 7) to examine both direct and indirect relationships between variables. The results indicate: (1) career exploration significantly and positively predicts career maturity; (2) professional commitment partially mediates the relationship between career exploration and career maturity; (3) future time perspective enhances the positive effect of professional commitment on career maturity, with more pronounced impacts observed in students with a high future time perspective. This study enriches SCCT by validating a context-specific mechanism within Chinese higher education and offers practical insights for optimizing university career guidance to better promote students’ career development.